Analisis kesalahan dalam memecahkan masalah soal cerita matematika materi bangun datar pada peserta didik kelas iv sekolah dasar - Avifah Salmahindun; Rukayah Rukayah; Siti Kamsiyati (Didaktika Dwija Indria, 2019)
Abstract. After conducting the result of interview and obervation, the researcher found that student’s mathematical performance is still not good. This study aims to describe student’s error according to Newman’s Error Analysis in solving word problem of geometry. This research used a qualitative approach with case study design and purposive sampling technique. Data were collected through diagnostic problem solving test and interview of fourth grade students in SDN 02 Gedongan. The results of this research showed that the most error made are in process skill and the fewest error made are in comprehension. Students in all categories did three types of error in solving word problem of geometry that were transformation, process skill, and encoding error. The most error Error analysis of students was expected educators to use the right way to solve it in the next lesson.Keywords: word problem, NEA, problem solving skills, geometry, elementary school